John Henry Newman : the challenge to evangelical religion - Turner, Frank M. (Frank Miller), 1944-2010 (Yale University Press, 2002)
One of the most controversial religious figures of the 19th century, John Henry Newman (1801-1890) began his career as a priest in the Church of England but converted to the Roman Catholic Church in 1845. He became a cardinal in 1879. Between 1833 and 1845 Newman, now best known for his autobiographical "Apologia Pro Vita Sua" and "The Idea of a University", was the aggressive leader of the Tractarian Movement within Oxford University. Newman, along with John Keble, Richard Hurrell Froude and E.B. Pusey, launched an uncompromising battle against the dominance of evangelicalism in early Victorian religious life. By 1845 Newman's radically outspoken views had earned him censure from Oxford authorities and sharp criticism from the English bishops. Frank Turner portrays Newman as a disruptive and confused schismatic conducting a radical religious experiment. This study demonstrates that Newman's passage to Rome largely resulted from family quarrels, thwarted university ambitions, the inability to control his followers, and his desire to live in a community of celibate males